The Impact of Green Marketing Mix on Determinants of Brand Equity: The Case of North Cyprus - Esfahani, Behrouz Ghazi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
These days sustainability is becoming a vital part of doing business in almost all industries due to the growing demand for environmentally friendly products. Moreover, people are conscious about product features and the way they are produced. This study investigates the relationship between green marketing mix and determinants of brand equity. Green marketing mix elements are consisting of green product, green price, green promotion and green place whereas brand equity determinants are defined as brand trust, brand loyalty and brand image. In order to collect data, convenience sampling method was used and total of 150 respondents from North Cyprus took part in this study. Descriptive analysis, t-test, ANOVA, correlation analysis, reliability test (Cronbach`s Alpha) and regression are conducted. The result of this study showed that almost all respondents are positive about the concept of green marketing. However, there is not any significate difference between the perception of male and female participants similarly, among people with different educational level. Green product and green price also seem to be the most important elements effecting brand equity. Keywords: green marketing mix, green marketing, green product, brand equity, Independent T-test and One-Way Anova Analysis

ÖZ: Bugünlerde sürdürülebilirlik, çevre dostu ürünlere olan talep nedeniyle neredeyse tüm sektörlerde iş yapmanın hayati bir parçası haline geliyor. Buna ilaveten, insanlar ürün özellikleri ve üretilme şekilleri konusunda her geçen gün bilinçleniyor. Çalışmada yeşil pazarlama karması ile marka değeri belirleyicileri arasındaki ilişki araştırılmaktadır. Yeşil pazarlama karması elemanları; yeşil ürün, yeşil fiyat, yeşil tanıtım ve yeşil alandan oluşmaktadır. Marka değeri belirleyicileri, marka güveni, marka sadakati ve marka imajı olarak tanımlanır. Veri toplamak için uygun örnekleme yöntemi kullanılmış ve bu çalışmaya Kuzey Kıbrıs'tan toplam 150 katılımcı katılmıştır. Tanımlayıcı analiz, t-testi, ANOVA, korelasyon analizi, güvenilirlik testi (Cronbach's Alpha) ve regresyon analizi kullanılmıştır. Bu çalışmanın sonucu neredeyse tüm katılımcıların yeşil pazarlama kavramı konusunda olumlu olduğunu göstermiştir. Ancak, erkek ve kadın katılımcıların benzer şekilde algıları arasında anlamlı bir fark yoktur. Yeşil ürün ve yeşil fiyat da marka hakkını etkileyen en önemli unsurlar olarak gözüküyor. Anahtar Kelimeler: Yeşil pazarlama karması, yeşil pazarlama, yeşil ürün, marka değeri, Bağımsız t testi ve tek yönlü anova analizi
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing Management; Green Marketing--Cyprus, North; Green marketing--Management--Industrial management--Environmental aspects; Green marketing--Environmentalist, conservationist & Green organizations; Green marketing--Product management - Environmental aspects; Green marketing mix; green marketing; green product; brand equity; Independent T-test and One-Way Anova Analysis